The factors for given equation are -2/3 and -2.
Rewriting the equation firstly -
3x² + 8x + 4 = 0
ax² + bx + c = 0
Factorizing the equation as per mentioned two rules -
6 and 2 are the suitable factors for given expression -
3x² + 6x + 2x + 4 = 0
3x (x + 2) + 2(x + 2) = 0
(3x + 2) (x + 2) = 0
3x + 2 = 0
3x = -2
x = -2/3
x + 2 = 0
x = -2
So, the two factors of equation are -2/3 and -2.
To check the factors, we will keep the value of x in equation -
When x = -2/3
3x² + 8x + 4 = 0
3(-2/3)² + 8(-2/3) + 4 = 0
3(4/9) - 16/3 + 4 = 0
4/3 - 16/3 + 4 = 0
Multiplying the equation with 3/4
1 - 4 + 3 = 0
- 3 + 3 = 0
0 = 0
When x = -2
3x² + 8x + 4 = 0
3(-2)² + 8(-2) + 4 = 0
12 - 16 + 4 = 0
- 4 + 4 = 0
0 = 0
Since for both values of x, Left hand Side and Right Hand Side of equation is same, the two resultant factors are correct.
Learn more about factorizing -
https://brainly.com/question/25829061
#SPJ4